Evidence for a Radical Mechanism in Cu(II)-Promoted SnAP Reactions - Luescher, Michael U.; Bode, Jeffrey W. (Synlett, 2019)
Saturated nitrogen heterocycles can be found with increasing abundance in bioactive molecules despite a limited number of methods to access these scaffolds. However, the coupling of recently introduced SnAP [tin (Sn) amine protocol] reagents with a wide range of aldehydes and ketones has proven to be a reliable, practical, and versatile one-step approach to saturated N-heterocycles. While effective, the lack of mechanistic understanding limits efforts to develop new catalytic and enantioselective variants. To distinguish between a polar or radical mechanism, we assessed Lewis and Brønsted acids, radical trapping experiments, and radical clock SnAP reagents reinforcing the current understanding of the SnAP protocol as a radical cyclization.
Keywords: SnAP reagents; N-heterocycles; morpholines; cyclization; radical clock; mechanism